Remarks on the genus Emeljanovianus Dlabola, 1965 (Hemiptera: Auchenorrhyncha: Cicadellidae), with description of a new species from Italy - Guglielmino, Adalgisa; Sanna, Francesco; Bückle, Christoph (Zootaxa, 2024)
Emeljanvianus hyperprocessatus sp. n. from Italy is described and illustrated. It is closely related to E. medius (Mulsant & Rey, 1855) and E. hilaris (Melichar, 1900) but is easily distinguished from these species by the structure of the male genitalia, specifically the aedeagus and the pygofer lobe process. Taxonomic problems concerning E. medius and E. hilaris and their distribution in the Palearctic region are discussed. The synonymy of E. medius and E. signatus (Haupt, 1917) is confirmed.